Assumptions of Customer Knowledge Enablement in the Open Innovation Process - Jokubauskienė, Raminta; Vaitkienė, Rimgailė (Economics and Business, 2017)
In the scientific literature, open innovation is one of the most effective means to innovate and gain a competitive advantage. In practice, there is a variety of open innovation activities, but, nevertheless, customers stand as the cornerstone in this area, since the customers’ knowledge is one of the most important sources of new knowledge and ideas. Evaluating the context where are the interactions of open innovation and customer knowledge enablement, it is necessary to take into account the importance of customer knowledge management. Increasingly it is highlighted that customers’ knowledge management facilitates the creation of innovations. However, it should be an examination of other factors that influence the open innovation, and, at the same time, customers’ knowledge management. This article presents a theoretical model, which reveals the assumptions of open innovation process and the impact on the firm’s performance.